A study of the mitochondrial DNA rearrangements in three interspecific somatic hybrids of Medicago sativa - Busti A.; Pupilli F.; De Marchis F.; Arcioni S. (Quality in lucerne and medics for animal production, 2001)
Restriction-fragment-length-polymorphism (RFLP) analysis showed that the M. sativa + M. coerulea hybrid retained all of the M. coerulea-specific bands but lost all the major M. sativa-specific bands. The M. sativa + M. falcata hybrid showed only M. sativa-specific bands together with non-parental bands, and the M. sativa + M. arborea hybrid showed a partial incorporation of bands from both parents together with non parental bands. The three different outcomes were attributed to differences in the genetic distance and cell cycles between the parents of each hybrid. Analysis of the sexual progeny of the M. sativa + M. coerulea hybrid showed that a residual mitochondrial DNA subunit of M. sativa was retained in the hybrid cytoplasm. This subunit was amplified and inherited in a mutually exclusive, allelic-like fashion with its M. coerulea homologous counterpart in the sexual progeny of the hybrid.
14. Réunion Eucarpia du Groupe Medicago spp., 2001/09/12-15, Zaragoza and Lleida (Spain)